GROWTH RESPONSE OF PAKCOY (Brassica rapa L.) WITH HYDROPONIC APPLICATION OF LIQUID ORGANIC FERTILIZER FRUIT WASTE - Azlina, Nor Aida; Sari, Mella Mutika; Istyadji, Maya (Transpublika Publisher, 2022)
Research on the application of fruit waste liquid organic fertilizer to the growth of pakcoy plants (Brassica rapa L.) has been carried out. The purpose of this study was to determine the growth response of the pakcoy plant (Brassica rapa L.) to the application of liquid organic fertilizer from fruit waste at various concentrations hydroponically and to determine the best concentration of liquid organic fertilizer for the research results. The design of this study used CRD (Completely Randomized Design) with experimental data collection methods. This research was conducted with one control treatment, 5 treatments and 4 replications namely D0 (100% AB mix), D1 (25%), D2 (40%), D3 (55%), D4 (70%) and D5 (85%). Data were analyzed statistically through ANOVA test and followed by 5% DMRT test. Based on the research results obtained, the application of liquid organic fertilizer from fruit waste had a significant effect on the growth response of pakcoy plants (Brassica rapa L.). This can be seen in the best treatment found in treatment D5 (85%), as evidenced by the highest average result of fruit waste liquid organic fertilizer at plant height: 22.075 cm, number of leaves: 20.25 leaves and fresh weight: 41. 25 gr/plant. Thus, the use of fruit waste as a POC affects the effectiveness of pakcoy growth.